Effect of Mean Arterial Pressure (MAP)-Based Preeclampsia Screening Training on Midwives’ Knowledge - Nidya Comdeca Nurvitriana; Devi Maya Arista; Karunia Wijayanti; Sri Wahyuni; Qatrunnada Naqiyyah Khusmitha (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Preeclampsia remains a major cause of maternal morbidity and mortality worldwide, making early risk identification an important component of antenatal care. Mean Arterial Pressure (MAP) has been recommended as a simple and cost-effective screening method for predicting the risk of preeclampsia. However, its application in primary healthcare settings remains limited. This study aimed to evaluate the effect of MAP-based preeclampsia screening training on midwives’ knowledge of early preeclampsia detection. Methods: A one-group pretest–posttest study was conducted among midwives participating in a MAP-based preeclampsia screening training program. Forty-two midwives attended the training, and 37 who completed both assessments were included in the analysis. The training covered the concept of MAP, accurate blood pressure measurement procedures, MAP calculation, and interpretation of MAP values for identifying women at risk of preeclampsia. Knowledge was assessed using a structured 20-item questionnaire administered before and after the training. Data normality was tested using the Kolmogorov–Smirnov test, and differences between pretest and posttest scores were analyzed using the Wilcoxon Signed Rank Test. Results: Knowledge scores improved following the training, with a mean increase of 3.35 points. Statistical analysis showed a significant difference between pretest and posttest scores (p = 0.018), indicating that the training effectively enhanced participants’ understanding of MAP-based preeclampsia screening. The findings suggest that a short structured educational intervention can improve knowledge related to early preeclampsia detection. Conclusion: MAP-based preeclampsia screening training significantly improved midwives’ knowledge regarding early detection of preeclampsia. Incorporating similar training into continuing professional development programs may strengthen early risk identification in maternal healthcare. Further studies with larger samples, control groups, and longer follow-up periods are needed to assess knowledge retention and clinical implementation.